Sistema de rastreamento do Circular da Unisinos utilizando LoRaWAN - Nedel, Everton (Universidade do Vale do Rio dos Sinos, 2019)
To facilitate user access to information and make better the services of the Unisinos Circular Line, it was deployed a system able to make a real time bus monitoring. The system, from a network LoRaWAN®, using radio frequency technology LoRa® transmit the localization data acquired from a GPS module to a server, that makes the data available in an interactive map. The system differential is work without a periodically cost, for example the generated by mobile phone plans, that is required by the GPS tracker founded in the market. The system worked perfectly but have limitation about the signal reach, having some points on the route, where with 1 km the communication got lost. On this way, it was identified that with only one LoRaWAN® gateway, the network didn’t cover all the Unisinos Circular area, where in some places, some data were lost, and, in some places, data were completely lost. So, it is needed to get a network extension with at least one more gateway for having its fully operation.
Keywords: Internet das coisas; LoRa®; LoRaWAN®; Rastreamento; Internet of things; Tracking